Photosensitization of bovine serum albumin by pterin: a mechanistic study - Thomas, Andrés Héctor (2013)
Pterins, heterocyclic compounds widespread in biological systems, are able to photoinduce oxidation of DNA and its components. In the present study, we have investigated the photosensitizing properties of pterin (Ptr), the parent compound of oxidized pterins, using bovine serum albumin (BSA) as target. Aqueous solutions of BSA were exposed to UV-A irradiation (350nm) in the presence of Ptr, under various experimental conditions. The photosensitized processes were followed by UV/vis spectrophotometry, an enzymatic method for H2O2 determination and electrophoresis (SDS-PAGE). We present data that demonstrate unequivocally that BSA is damaged by Ptr. Although association between Ptr and the protein was evidenced by steady-state and time-resolved fluorescence measurements, the photosensitized damage takes place via a purely dynamic mechanism, which involves an electron transfer from BSA to the triplet excited state of Ptr, formed after UV-A excitation.